Impact on health outcomes of hemodialysis patients based on the experience level of registered nurses in the hemodialysis department: a cross-sectional analysis - Jeong, EunYoung (Frontiers in Health Services, 2023)
Background: The aim of the study is to improve the policy of health authorities regarding registered nurses (RNs) staffing by understanding how the health outcomes of hemodialysis (HD) patients vary depending on the level of HD nursing experience of at least two years. Methods: The study included 21,839 patients who started maintenance HD for three months in early 2013 in the same medical institutions. Demographic variables such as sex, age, and causes of HD; institutional variables such as type of institution and number of RNs; and health outcomes such as HD adequacy, systolic and diastolic blood pressure (SBP, DBP), hemoglobin(Hb), and serum albumin were collected through web-based questionnaires. To determine the relationship between variables, t-test, chi-square test, and ANOVA were employed. Binary logistic regression was used to examine the odds ratio. Results: Institutions with 100% of experienced RNs with at least two years of experience in HD units were found to have higher NKF K-DOQI criteria satisfaction rate than Institutions with <50% of experienced RNs with at least two years of experience in HD units for all health outcomes, except DBP (42.9% vs. 38.8%, p<.001) and Hb (27.8% vs. 24.4%, p<.001). Four of the six health-related variables—HD adequacy (Kt/v, urea reduction rate, URR), SBP, and serum albumin—were higher in institutions with 100% of experienced RNs than those with less than 50%. Conclusions: In order to improve HD patients’ health outcomes, HD institutions should prioritize recruiting RNs who are proficient in HD care. A higher proportion of skilled RNs results in a higher ability to prepare for emergencies and early detection of patient complications. RNs with extensive experience in HD nursing, therefore, promote quality management of HD patients.